Automatic Matching of Software Component Requirements Using Semi-Formal Specifications and a CBSE Ontology - Andreou, Andreas S. (My University, 2026)
Short listed for best paper award at the 10th International Conference on Evaluation of Novel Approaches to Software Engineering (ENASE).
Keywords: Sciences